HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN TINGKAT STRES - Nabila Rezki, Anisa; Naryoso, Agus; Pradekso, Tandiyo (Interaksi Online, 2024)
Social media is an online platform that allows users to share content, interact and connect virtually. Global social media usage in 2022 reached more than 4.59 billion and is expected to grow to 6 billion by 2027. However, the rapid growth of social media has raised concerns about its impact on psychological well-being. Currently, there are many cases of depression and suicides due to mental health in various regions. Therefore, this study aims to determine whether there is a relationship between the intensity of social media use (Youtube, Facebook, Tiktok, and Instagram) and stress levels. The sample set amounted to 120 respondents with the criteria of age 18-34 years who actively use social media (Youtube, Facebook, Tiktok, and Instagram) and live in Semarang City.  This study used non-probability sampling. The results of this study indicate that there is a positive relationship between the intensity of social media use and stress levels. The hypothesis is proven by the results of multiple correlation tests with a significance value <0.05, namely 0.026, which means that the value is significant and the correlation coefficient between the two variables is 0.302, which means that the relationship between the two variables is positive and falls into the weak category.